Antipruritic Effect of Ethyl Acetate Extract from Fructus cnidii in Mice with 2, 4-Dinitrofluorobenzene-Induced Atopic Dermatitis. (7th May 2020) - Chen, Xi; Zhu, Chan; Zhang, Yingge; Yang, Niuniu; Shi, Hao; Yang, Weiwei; Yang, Yan; Liang, Jianqiang; Chen, Liuzhi; Zeng, Xueying; Cai, Rijin; Wu, Guanyi; et al.
Abstract : Atopic dermatitis (AD) is a common inflammatory skin disease characterized by intense pruritus and skin lesions. The exact cause of AD is not yet known and the available therapeutic strategies for AD are limited. Fructus cnidii is commonly used in traditional Chinese medicine as an herb for treating chronic itch. However, the mechanism underlying the antipruritic effects of Fructus cnidii is not well understood. In the present study, we investigated the antipruritic effect of locally administered ethyl acetate extract from Fructus cnidii (EAEFC) to 2, 4-dinitrofluorobenzene- (DNFB-) induced AD in a mouse model. The scratching behavior, skin thickness, dermatitis score, weight, blood immunoglobulin E (IgE) level, and itch-related cytokine levels were subsequently monitored and evaluated. Results showed that EAEFC treatment attenuated the DNFB-induced AD-like symptoms by alleviating the skin lesions and decreasing the dermatitis score. Hematoxylin and eosin (H&E) and toluidine blue (TB) staining analyses demonstrated that EAEFC mitigated the DNFB-induced increase in skin thickness and prevented the infiltration of mast cells. Behavioral tests showed that EAEFC decreased the DNFB-induced acute and chronic scratching behaviors. Furthermore, EAEFC reduced the levels of itch-related cytokines, such as thymic stromal lymphopoietin (TSLP), interleukin- (IL-) 17, IL-33, and IL-31, and the DNFB-induced boost in serum IgE. Collectively, these results suggest that EAEFC is a potential therapeutic candidate for the treatment of chronic itch in AD.